Influence of Work Environment and Leadership Style Transformational to Employee Performance With Professionalism as an Intervening Variable In Pengadilan Negeri Jambi Kelas IA - Yani, Asminar Fitri; Suryani, Arna; Yamali, Fakhrul Rozi (Universitas Batanghari, 2024)
The purpose of this study is to describe the work environment, transformational leadership style, professionalism and employee performance at Jambi District Court Class IA. Then to analyze the influence of the work environment and transformational leadership style on professionalism, analyze the work environment and transformational leadership style on employee performance, then analyze the influence of professionalism On employee performance, then analyze the influence of the work environment and transformational leadership style through professionalism on employee performance. This research is a research using descriptive and verifiative research methods, which is a method in examining a group of people, an object, situation and condition of a system of thought with a goal to make a description, a systematic picture according to the facts being investigated. The verification research aims to test hypotheses about the influence between variables of this study. This study involved employees at the Jambi District Court Class IA and for a sample of 84 people. Data was analyzed using SPSS.22. The results showed that the work environment is in good condition, transformational leadership style in high conditions, professionalism and employee performance are also high, that the work environment , and transformational leadership style are simulatively or partial has a positive and significant effect on professionalism, work environment and transformational leadership style simultaneously and partially has a positive and significant effect on employee performance, and professionalism has a positive and significant effect on performance employee at Jambi District Court Class IA. To be able to improve the professionalism of its employees at work by providing rewards, promotions so that they can work better for the progress of the agency. In addition, it also provides sanctions to employees who do not carry out their duties and responsibilities properly. In addition, it also provides services in the field of law to people who seek justice for the legal problems they face